Design system and performance analysis of fish storage box by utilizing solar energy - Setiawan, Rizal Justian; Ma'ruf, Khakam; Darmono, Darmono; Suryanto, Indra Dwi; Hermawan, Andi Tri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Indonesia is a maritime country and many people work as traditional fishermen. Traditional fishermen generally use thermos filled with wet ice, ice boxes, or ice blocks to maintain the freshness of fish. The temperature obtained is still insufficient to maintain the fish’s quality and freshness. Furthermore, some existing technologies are expensive and use fossil fuels. Researchers designed and manufactured a cool box that utilizes solar energy to store fish. The experimental research method was conducted by testing the performance of the cool box device at four different locations. The results showed that the solar panel produced an average of 2,527.2 W of energy in a day, which can power the cool box device for 10 hours. To maintain the fish’s freshness with the reference temperature of 0 °C-5 °C, the device uses temperature control to prevent the fish from freezing, which damages its structure. The temperature control also helps the tool save energy, allowing it to last 170 minutes longer than without using the temperature control feature.